Juridical Analysis Regarding Changes in The Regulations on Adultery in Law Number 1 of 2023 Concerning The Criminal Code in Indonesia - Mutiara Ambar Solichah; Hanifah Febriani; Tomás Mateo Ramon (Proceeding International Conference Restructuring and Transforming Law, 2023)
This research aims to explain the comparison of adultery regulations in the old Criminal Code and the new Criminal Code, as well as the implications of changes to the adultery regulations in the new Criminal Code. The research method is normative. This research is a type of normative research that uses secondary data. The approach taken is a statutory and conceptual approach. The data analysis method used is qualitative. The results of this research are regarding adultery in the old Criminal Code which is regulated in Article 284 of the Criminal Code, which provides the meaning of adultery only between a man and a woman, one of whom is at least married, while the new Criminal Code is regulated in Article 411 of the Criminal Code, which expands the meaning of adultery. also covers men and women who are not related by marriage, who are threatened with imprisonment for a maximum of 1 (one) year. Adultery is a complaint offense in both the old and new Criminal Code, but in the new Criminal Code there are additional parties who can file a complaint about adultery, namely not only husband/wife, but also parents and children for people who are not related by marriage, in addition there is an increased threat of imprisonment in the new Criminal Code, namely for 1 (one) year. The implications of the changes to the regulation of adultery in the new Criminal Code are to minimize opportunities for adulterous behavior that could potentially be committed by married young couples, to apply customary law in Indonesia and to abandon western concepts, namely the Netherlands, to realize responsive criminal law, meeting the needs of Indonesian society. religious, and minimizing the presence of vigilantism by society, provides a deterrent effect because there are increased criminal penalties for perpetrators of adultery.